Teaching Writing Using E-Portfolio: It’s Effect on Students' Writing Ability - Masrul, Masrul; Nurmalina, Nurmalina (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Electronic portfolio is a big system that can be employed for educational and employment purposes. This study examined the effects of using an electronic portfolio (e-portfolio) in improving students’ writing ability. This quasi experiment involved 100 students from the State University of Malang (58 women and 42 men) as subjects. The results showed that students in the experimental group outperformed the students in the control group. Task achievement, coherence and cohesion, lexical resource, grammatical range and accuracy, overall score, relevant, valid, authentic, recent, transferable, sufficiency, and at least at higher vocational level were the indicators used in this study. It was found that coherence and cohesion, grammar range and accuracy, and overall score did not differ significantly.